IMPROVEMENT IN BENEFICIATION OF Low GRADE FLUORITE ORE FROM KALAT MARAN RANGE - Gohar, R A; Kazmi, K R; Hafeez, A; Anwar, Shafique (Biological Sciences - PJSIR, 2002)
This paper describes a bench scale investigation on the preparation of metallurgical and chemical grade fluorspar concentrate from a low-grade fluorite ore from Kalat Maran Range. A combination of chemical treatment and flotation techniques has been applied to fluorite ore. The ore initially containing 36.5% calcium fluoride has been processed and benefic1ated to produce calcium fluoride concentrate containing 98.7% calcium fluoride with 99.8% recovery.